Severity of Coronary Artery Disease in Diabetic and Non-Diabetic Patients Presenting with Non-ST Elevation Myocardial Infarction: CVD in Diabetic and Non-Diabetic Patients with Non-ST Elevation Myocardial Infarction - Bibi, Ayesha; Khan, Matiullah; Anwer, Bushra; Qasim, Muhammad; Irshad, Usama; Iqbal, Mohsin (Pakistan Journal of Health Sciences, 2025)
Diabetes mellitus accelerates coronary artery disease (CAD) and may worsen outcomes in non–ST–elevation myocardial infarction (NSTEMI). However, data from South Asia comparing lesion complexity and left ventricular function in diabetic vs non-diabetic NSTEMI patients remain limited. Objectives: To compare angiographic complexity (SYNTAX score), lesion severity, and left ventricular ejection fraction (LVEF) between diabetic and non-diabetic NSTEMI patients. Methods: This analytical cross-sectional study was conducted over 2 months (June -August, 2025) and included 83 consecutive NSTEMI patients (41 diabetics, 42 non-diabetics). All underwent coronary angiography for SYNTAX scoring and echocardiography for LVEF. Continuous variables were compared using t-tests with 95% confidence intervals and Cohen’s d, and categorical data were analyzed using Chi-square/Fisher’s exact test with Cramér’s V. Results: Diabetics had significantly higher SYNTAX scores (24.1 ± 5.9 vs 19.2 ± 5.0; mean difference 4.86, 95% CI 2.46–7.25, Cohen’s d = 0.87) and more frequent severe stenosis (61.0% vs 33.3%; p=0.012, Cramér’s V = 0.28). LVEF was significantly lower in diabetics (46.9 ± 7.6% vs 53.7 ± 6.2%; mean difference −6.84, 95% CI −9.87 to −3.81, Cohen’s d = 0.97). Rates of heart failure, arrhythmia, and mortality did not differ significantly (p>0.05). Conclusions: Diabetic NSTEMI patients demonstrate greater anatomic complexity and impaired ventricular function compared to non-diabetics, yet short-term outcomes remain comparable when standardized guideline-directed therapy is applied. These findings underscore the importance of early risk stratification and consideration of adjunctive prognostic markers such as inflammatory indices in this high-risk group.